Clinical Effects of a New Dental Rinse Containing Cetylpyridinium Chloride and Tranexamic Acid on Periodontal Disease - KAWAJIRI, Katsuhiko; YAMAZAKI, Seiji; YAMADA, Takashi; KAMIJYO, Hiroyuki; SAKAMOTO, Hiroshi; TAKAHASHI, Kazuo; ITO, Shigeki; OTA, Norio; KISHIMOTO, Shin; NOMURA, Toshi; KAWATANI, Kazuhiko; OZAWA, Yoshihiko; et al. (Nihon Shishubyo Gakkai Kaishi (Journal of the Japanese Society of Periodontology), 1994)
The purpose of this study was to evaluate the clinical effect of a new dental rinse containing 0.02% Cetylpyridinium chloride and 0.05% Tranexamic acid on the prevention of periodontal disease (prevention of plaque and improvement of gingivitis). The rinse was formulated without nonionic surfactant so as to improve the efficacy of Cetylpyridinium chloride. The study was conducted using a double-blind design with 63 healthy subjects for four weeks. Gingival index (GI) and plaque index (P1I) on 62/4 /4/26 were examined at baseline, and at 1, 2 and 4 weeks after treatment. The following results were obtained; 1. Improvement of PlI was statistically higher in thc tcst rinse group than in the placebo rinse group for all examination periods (P<0.001). 2. Improvement of GI was statistically higher in the test rinse group than in the placebo rinse group for all examination periods (P<0.01). 3. No adverse effects were observed during the study in any of the subjects. The results indicate that a new dental rinse containing Cetylpyridinium chloride, as an anti -microbial agent, and Tranexamic acid, as an anti -inflammatory agent, has superior effects in preventing periodontal disease (prevention of plaque and improvement of gingivitis).